Synthesis, Characterization and Antioxidative Activity of Metal Complexes with Rhein - Zhao, F.; Liang, H.; Cheng, H.; Wang, J.
Three metal complexes with rhein ML 2 2H O [L=rhein (1-OH group deprotonated)]; M= Cu(II), Fe(II), Mn(II)] have been synthesized and characterized by elemental analysis, molar conductance, IR, 1 2 H NMR, TG-DSC and UV-Vis spectroscopic techniques and by fluorescence analysis. The scavenging effect on the superoxide radical (O 2 - ), hydroxyl radical (OH), DPPH were also compared. The metal complexes are stronger than rhein for antioxidant activity.
Keywords: RHEIN; METAL COMPLEXES; SYNTHESIS; ANTIOXIDATIVE ACTIVITY